About Emotions: Array - Filip, Raluca (New Trends in Psychology, 2020)
The existence of emotional control centers in our heads arouses visions of a race of robots created by “nature” to feel and behave in a certain way. Our conscious self - interested in career, personal happiness or something else - must negotiate a compromise within the nervous circuits between what we “know” and the ancient knowledge, ready “configured” in the limbic system. Would this explain the ambivalences and paradoxes that have intertwined a “model” or a theory of the human mind? In a way, conflicts are inherent in the system; what we want for ourselves may not depend on the development of the species. (Dr. Richard RESTAK, The Brian, the last frontier) Mindfulness, in its most general sense, refers to waking up from a life lived on autopilot and being interested in what our daily experiences bring to our attention. (...) When we are mindful (conscious) we live HERE and NOW, we are aware of our own thoughts and feelings, being also receptive to those of the people around us (Gaspar & Urban, p. 23).